Effects of Financial Education Training on the economic wellbeing of social business - Flores Anaya, Yadira Zulith; Salinas Solís, Karina Isabel; Sorzano-Rodríguez, Deisy Milena (My University, 2023)
Social microenterprises play an important role in the economy, as they are recognized as the key engine of economic growth in developing countries, however, the lack of financing remains one of their main obstacles. The objective of this paper is to analyze the effect of financial education given to microentrepreneurs on economic profitability, as well as other specific characteristics of microentrepreneurs and their businesses. Data from financial logs applied to social microenterprises in the city of Tijuana, Baja California, Mexico are used; in which the sales, costs and operating expenses of the business are recorded daily for four weeks. Through a linear regression analysis and the Wilcoxon Signed Ranks Test method, it is found that financial education training has a positive effect on the net profits of the business; addition to the positive increase in their sales by transitioning to using technology to advertise or sell their products; the use of credit ends up making visible that in many cases it harms the business because it cannot be used properly. RESUMEN Las microempresas sociales juegan un papel importante en la economía, ya que son reconocidas como el motor clave del crecimiento económico en los países en desarrollo, sin embargo, la falta de financiamiento sigue siendo uno de sus principales obstáculos. El objetivo de este trabajo es analizar el efecto de la educación financiera impartida a los microempresarios sobre la rentabilidad económica, así como otras características específicas de los microempresarios y sus negocios. Se utilizan datos de bitácoras financieras aplicadas a microempresas sociales en la ciudad de Tijuana, Baja California, México; en el cual se registran diariamente durante cuatro semanas las ventas, costos y gastos de operación del negocio. Mediante un análisis de regresión lineal y el método de Prueba de Rangos con Signos de Wilcoxon, se encuentra que la formación en educación financiera tiene un efecto positivo en las utilidades netas del negocio; además del aumento positivo en sus ventas al hacer la transición al uso de tecnología para publicitar o vender sus productos; el uso del crédito acaba por visibilizar que en muchos casos perjudica al negocio porque no se puede utilizar adecuadamente.
Gestión y Desarrollo Libre
Year 8,N° 15, january-June 2023
Keywords: Financial Education; Social Business; Financial Inclusion; Poverty; Campus Tijuana